Electronic Dustbin for Hospital Operation Theaters - Yan, Lee Wen (International Journal of Advanced Science and Technology, 2020)
The main aim of this project is to develop an electronic dustbin for the Hospital operation theaters that could reduce injuries cause by medical sharp due to improper medical waste disposal through the use of metal detection. Arduino Uno was used to perform medical waste segregation and medical waste management with GSM module. The performance of the developed proposed system is evaluated by testing the accuracy of both ultrasonic sensor’s distance obtained and servo motor’s angular position provided, the time taken for message to reach mobile phone, the time taken to complete trash segregation and metal segregation process. It is observed that the average accuracy for ultrasonic sensor is 98.9%, while the average accuracy for servo motor is 91.16%. The shortest time taken for message to reach mobile phone is 7.25 sec, while the shortest time taken to complete trash segregation and metal segregation process is 5.5 sec and 5.56 sec respectively. The possible improvement of the proposed system is improving the sensitivity of the metal detector to increase range of detection.